2002
DOI: 10.1081/cbi-120005390
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Morningness–eveningness Preference

Abstract: Morningness-eveningness preference (morning-, intermediate-, evening-type) or circadian typology is the individual difference that most clearly explains the variations in the rhythmic expression of biological or behavioral patterns. The aim of this study was to analyze gender difference in morningness-eveningness preference using the Horne and Ostberg questionnaire in the largest university student population selected so far (N = 2135), with an age range 18-30 yr. Morningness-eveningness questionnaire (MEQ) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
228
9
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(294 citation statements)
references
References 25 publications
23
228
9
16
Order By: Relevance
“…The distribution approximates a normal curve, with a skewness of 0.005 and a kurtosis of -0.4. (Table 2) compares the typology distribution of our study participants with that of four participants of other studies that used the MEQ to investigate the status of college students of the same age group in Spain, Italy, Germany and the United States 1114. Morning typology was more common in Saudis, particularly males, than reported in some Western countries.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The distribution approximates a normal curve, with a skewness of 0.005 and a kurtosis of -0.4. (Table 2) compares the typology distribution of our study participants with that of four participants of other studies that used the MEQ to investigate the status of college students of the same age group in Spain, Italy, Germany and the United States 1114. Morning typology was more common in Saudis, particularly males, than reported in some Western countries.…”
Section: Resultsmentioning
confidence: 93%
“…Previous reports of gender effects on chronotype have been inconsistent. Some investigators have reported a higher prevalence of morningness in females, but other studies found no between-gender differences 111416. Chronotype has also been reported to be related to personality characteristics.…”
Section: Discussionmentioning
confidence: 94%
“…During the adulthood, CS is mature, but gender differences appear during this period related to chronotype (Adan and Natale 2002). Finally, aging is associated with a phase advance, fragmentation, and flattening of marker rhythms (robust, easy-to-register, noninvasive, and comfortable circadian rhythm driven by the circadian pacemaker) (Hofman and Swaab 2006;Van Someren et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Women reach their maximum in lateness at around 19.5 years of age, 25 while men continue to delay their sleep until around the age of 21 and are, on average, later chronotypes for most of their adulthood (see also Ref. 37 ). This sex (rather than gender) difference disappears at around the age of 50, which coincides with the average age at menopause.…”
Section: Chronotype and Agementioning
confidence: 99%